Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae) - Kiss, Ádám; Choi, Sei-Woong; Han, Hui-Lin (Zootaxa, 2018)
This paper deals with the taxonomy of the genus Narcotica Sugi, 1982, known from China, Japan and the Korean Peninsula. Two species, Narcotica cryptica sp. n. from China and South Korea and Narcotica hoenei sp. n. from China are described as new to science. Images of adults, genitalia and, for the first time, abdominal segments of both sexes are presented.